2015
DOI: 10.4236/oalib.1101211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implant Diameter and Length on Stress Distribution for Titanium and Zirconia Implants by Using Finite Element Analysis (FEA)

Abstract: Purpose: The purpose of this study was to analyze stress distribution patterns in implant restorations created in different length and diameter made of titanium and zirconia by using three dimensional finite element analysis (FEM) with straight and 15˚ angled abutment. Materials and Methods: For titanium models; Ti-6Al-4V for implant fixture, connection element and abutments (straight and 15˚ angled abutment), yttrium tetragonal zirconium polycrystal (Y-TZP) for zirconium framework, Felds phatic porcelain for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In accordance with results obtained by previous studies,[2514] this study confirms that an increase in implant diameter and length reduces the stress magnitudes within cortical bone. The results of this study confirm the conclusion of various studies[251415] that implant diameter is an effective design parameter than implant length. In this study, Von Mises stress distributions at the implant–bone interface was localized in the cortical bone around the implant neck in all the models similar to findings of studies done previously.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with results obtained by previous studies,[2514] this study confirms that an increase in implant diameter and length reduces the stress magnitudes within cortical bone. The results of this study confirm the conclusion of various studies[251415] that implant diameter is an effective design parameter than implant length. In this study, Von Mises stress distributions at the implant–bone interface was localized in the cortical bone around the implant neck in all the models similar to findings of studies done previously.…”
Section: Discussionsupporting
confidence: 90%
“…[ 13 ] Yeşildal et al suggested increase implant diameter over length for success. [ 14 ] Abraham et al found lower compressive and tensile stresses in the peri-implant bone in the RP model compared to the NP model. [ 15 ] Topkaya et al concluded that implant length and diameter are important in its success.…”
Section: Discussionmentioning
confidence: 99%
“…The structure parameters can be set as any value. However, the materials of dental implant can only be selected from several Ti alloys, so the material parameters of dental implant are limited [26][27][28][29].…”
Section: Problem Descriptionmentioning
confidence: 99%